PERBAIKAN MUTU GENETIK ITIK LOKAL MELALUI TEKHNOLOGI BREEDING DI KELOMPOK TERNAK MONG GLEMONG, KELURAHAN DASAN CERMEN MATARAM - Asnawi Asnawi; Dwi Kusuma Purnamasari; I Ketut Gde Wiryawan (Jurnal Abdi Insani, 2023)
The ducklings of the Mong Glemong livestock group were obtained from self-breeding results from local mating of local ducks, so that the productivity of the breeds was still low. In order to obtain good quality ducklings, breeders have difficulty because of the NTB Governor's Decree No. 94 and No. 99 of 2007 concerning control of poultry traffic, especially concerning the prohibition of the entry of poultry originating from areas infected with avian influenza viruses such as Bali. To improve the quality of laying ducks through breeding technology in the Mong Glemong livestock group, Dasan Cermen Village, Mataram. Method: The approach to realizing the program is a participatory method, that is, each activity is carried out jointly with partners. Participation of partners in program activities is to provide locations where activities are carried out and participate in all programmed activities, while the proposer provides the necessary duck seeds and feed as well as technical guidance. Result: The program that has been designed together with group members is running well, and the benefits have been felt very positively by the group. The results obtained include the availability of special nursery cages for each group member, 2). Availability of hatching room for duck eggs in groups, 3). Availability of adequate incubator to incubate eggs. Conclusion: Currently, duck breeders in the "Mong Glemong" livestock group can produce good hatching eggs and ducklings.